Pengaruh Technology Acceptance Model (TAM) terhadap minat investasi FinTech dengan persepsi risiko sebagai faktor moderasi - Chandra, Kezia Trifena; Tanaamah, Andeka Rocky (AITI, 2025)
The rapid growth of the industry has generated significant interest in peer-to-peer (P2P) lending platforms, especially among students in Indonesia. This study investigates the factors influencing students' interest in investing through P2P lending, focusing on perceptions of ease of use, usefulness, and risk. The Technology Acceptance Model (TAM) is the framework for analyzing these variables' relationships. Additionally, the study examines the moderating role of risk perception on the relationship between perceived ease of use and usefulness with investment interest. Data collection involved distributing questionnaires to students nationwide, with data processed using Structural Equation Modeling (SEM) through the Smart-PLS application. The research findings suggest that perceived ease of use and usefulness significantly impact investment interest in P2P lending.